Analisis Kadar Formalin pada Mie Basah yang Dijual oleh Pedagang Bakso di Kota Sorong Menggunakan Spektrofotometer UV-Visible - Zf, Siti Fatma; Astuti, Ratih Arum; Hardia, Lukman (MES Bogor, 2024)
Noodles are a popular food among middle class people, both upper and lower classes because they taste delicious and are affordable. Wet noodles have a short shelf life due to their high water content, this is what encourages some sellers to use formaldehyde as a preservative. This examination means to decide if there is formalin content in examples of wet noodles sold by meatball brokers in Sorong City. Formalin investigation was completed subjectively and quantitatively. Subjective tests were done by adding chromatogenic corrosive to wet noodle tests and quantitative tests were completed to see the degree of formaldehyde contained in the examples utilizing an UV-noticeable spectrophotometer. The consequences of the subjective test showed that one example with code (S1) was recognized as sure for containing formaldehyde, which was demonstrated by the adjustment of the shade of the filtrate from brown to purple subsequent to being dribbled with chromatophic corrosive reagent and warmed in bubbling water. The total formalin content contained in sample S1 was 0.905%.